#### Answer

E. -4

#### Work Step by Step

We know that $\sqrt[3] 64=4$, because $4^{3}=4\times4\times4=64$.
Therefore, $-\sqrt[3] 64=-(4)=-4$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

E. -4

We know that $\sqrt[3] 64=4$, because $4^{3}=4\times4\times4=64$.
Therefore, $-\sqrt[3] 64=-(4)=-4$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.